ОСНОВНЫЕ ТЕНДЕНЦИИ РАЗВИТИЯ МАГНИТНО-ПОЛУПРОВОДНИКОВЫХ ГЕНЕРАТОРОВ ИМПУЛЬСОВ - Зозулев, В.И.; Шолох, Д.А.; Кобыльчак, В.В.; Христо, А.И. (Інститут електродинаміки НАН України, Київ, 2016)
The results of research and systematization of publications, which summarize the main trends in the further development of modern high-voltage semiconductor magnetic-pulse generators in the nanosecond range are set out. The main new and specific nodes of generators that determine the improved performance was considered. Seven main trends in the development of semiconductor magnetic-pulse generator was formulated. References 10, figures 5.